Sensor Technology for Improving the Safety and Performance of Electric Vehicle Battery Management Systems - Yu, Haonan (International Journal of Energy, 2025)
With the rapid development of electric vehicles, the safety and performance of battery management system (BMS) has already become a worldwide problem. The performance, life and safety of a car battery have a direct impact on the overall reliability and user experience of the car. This paper discusses the application of advanced sensor technology to improve the safety and performance of electric vehicle BMS. The influence of different kinds of sensors, such as temperature, voltage, current and gas sensors, on real-time monitoring, failure detection and battery performance optimization were discussed. It also explores the potential of sensor integration, predictive maintenance and smart charging management for accurate estimation of state of charge (SOC) and state of health (SOH). The study indentified important challenges regarding the regarding the precision, cost and environmental adaptability of sensors and suggested the future direction that can meet the needs of the nesxt generation BMS systems. This study provides insights that could enhance the safety and efficiency of BMS through sensor technologies critical to the performance and safety of future electric vehicles.